Aguamiel, a Traditional Mexican Beverage: A Review of Its Nutritional Composition, Health Effects and Conservation - Alma Delia Noriega-Juárez; Libier Meza-Espinoza; María de Lourdes García-Magaña; Rosa Isela Ortiz-Basurto; Martina Alejandra Chacón-López; Luis Miguel Anaya-Esparza; Efigenia Montalvo-González (Foods)
Aguamiel is the sap extracted from various species of maguey (Agave spp.). This liquid is highly prized in central Mexico for its pleasing sensory qualities and nutritional value. Understanding the composition of aguamiel is crucial as it may offer beneficial effects for human health. Reports have indicated its significance as a source of essential amino acids, vitamins, minerals, and fructooligosaccharides with prebiotic potential. Additionally, aguamiel can harbor diverse microorganisms, including lactic acid bacteria (Lactococcus and Leuconostoc spp.) and yeasts, contributing antioxidant, nutritional, prebiotic, and probiotic properties. However, aguamiel is prone to rapid fermentation due to its nature, which can alter its sensory and nutritional characteristics. This review provides insight into the broad nutritional composition, microbial diversity, and metabolites beneficial to the human health of fresh aguamiel. At the same time, it reviews the technologies applied to aguamiel to preserve its nutritional properties and functional metabolites and extend its shelf life. Thus, the data included in this document may lead to greater beverage consumption and further research to find new conservation alternatives that change its organoleptic and functional properties as little as possible.